The impact of weight self-stigma on appearance anxiety among female college students: a variable-centered and person-centered analysis - Xiang, Luyao; Gou, Hao; Hu, Chang (Frontiers in Public Health, 2025)
BackgroundAppearance anxiety and weight self-stigma have become increasingly prominent issues among female university students. However, existing studies have primarily concentrated on direct associations at the variable level, with limited exploration of heterogeneous subgroups from a person-centered perspective. This study aimed to examine the mediating role of body image in the relationship between weight self-stigma and appearance anxiety and to identify potential latent categories of weight self-stigma and body image, thereby providing scientific guidance for the prevention and improvement of appearance anxiety in female university students.MethodsFrom November 2024 to March 2025, a purposive sampling strategy was employed. A total of 1,368 female university students were recruited from 12 comprehensive universities located in six provinces of central and southern China (Hunan, Guizhou, Yunnan, Guangdong, Jiangxi, and Jiangsu). Participants completed the appearance anxiety scale, the weight self-stigma questionnaire, and the body image scale.Results(1) Weight self-stigma positively predicted appearance anxiety among female university students, with body image playing a partial mediating role (β = 0.250, p < 0.001); (2) Three latent patterns of weight self-stigma and body image were identified: low stigma—high body image (23.4%), moderate stigma-moderate body image (27.7%), and high stigma—low body image (48.9%); (3) Compared with the “low stigma—high body image” group, the other two categories significantly and positively predicted appearance anxiety (p < 0.001).ConclusionWeight self-stigma and body image among female university students demonstrate notable heterogeneity, and body image serves as a mediator in the relationship between weight self-stigma and appearance anxiety.